PENDAMPINGAN TRANSFORMASI DAUN MANGROVE MENJADI PAKAN TERNAK DAN PUPUK ORGANIK DALAM MENDUKUNG BLUE ECONOMY DI DESA TENGKET, KABUBAPATEN BANGKALAN - Muh Syarif; Agus Romadhon; Selamet Joko Utomo; Iffan Maflahah; Fathor AS; Lailatul Maghfiroh; Alung Febri Permadani (Jurnal Abdi Insani, 2025)
Mangroves are a coastal resource with significant potential but are underutilized, particularly mangrove leaves, which are often wasted. This community service activity aims to assist residents of Tengket Village, Bangkalan Regency, in processing mangrove leaves into animal feed and organic fertilizer, supporting the blue economy concept. The methods used included outreach, training, hands-on practice, and mentoring in the use of a mangrove leaf shredding machine. The results of the activity demonstrated increased community knowledge and skills in mixing feed and fertilizer, their ability to use the machine, and their awareness of the sustainable use of local resources. The resulting products are animal feed made from mangrove leaves (Rhizophora apiculata; Rhizophora mucronata) and organic fertilizer, which have proven suitable for use and have created new business opportunities that can increase community income. Participants' responses also reflected high enthusiasm, despite challenges such as limited initial capital and limited technical knowledge. Overall, this program plays a role in increasing the economic independence of coastal communities while preserving the mangrove ecosystem. For the program's sustainability, additional support related to product marketing, machine maintenance, and collaboration with the government and the private sector is recommended.